RANCANG BANGUN PROTOTIPE SISTEM MANAJEMEN BATERAI PADA MOBIL LISTRIK NEO BLITZ 2 MENGGUNAKAN MIKROKONTROLER - Putra, Dhimas Abdillah; Sujono, Sujono (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
In this study, a battery management system for the neo blitz 2 electric car was made using the Arduino Mega 2560 microcontroller. The battery used is a VRLA type 12 V 3 Ah battery which is commonly used on motorbikes. To be able to maintain battery performance, a battery management system is needed that is able to prevent overcharge, overdischarge and overload. In designing this battery management system uses a voltage sensor when recharging and a voltage sensor when discharging, a current sensor when recharging and a current sensor at discharge, a relay and a Solid State Relay to change the charge or discharge mode, and a 20x4 LCD for monitoring battery conditions. Research battery management system has been designed to automatically control battery usage to maintain battery performance. The test results of the sensors used can detect parameters with an error of each sensor below 3%. The protect overcharge system is able to run because when the battery reaches a voltage of 12.8 V the battery relay will turn off but the other battery relay will remain on until the battery reaches a voltage of 12.8 V and the overdischarge protect system is able to run because when the battery is detected weak or has an excess load then the Solid State Relay will be off and the LCD will display the code